STATE INSTITUTIONS AND ETHNIC IDENTITY OF PUNJABIS IN MODERN PAKISTAN - Zharbossynova, Н.Д. (Journal of Oriental Studies, 2024)
The article analyzes the role of state policy in solving ethnic problems on the example of Punjabis, taking into account the ethnic structure and historical specifics of Pakistani society. In this article, the authors discusses the legislative acts of the Islamic Republic of Pakistan, regulating the relations connected with the preservation and development of cultural identity of national and ethnic minorities, the preservation and development of regional language, as well as defining the tasks and competency of public administration bodies and units of local self-government in the area of these questions. Using the example of Pakistani Punjabis, the author analyzes the processes of interaction between official state institutions and ethnic groups. The development of globalization processes in the modern world actualizes the problems of ethnic identity and interethnic communications. On the one hand, the process of globalization is blurring the boundaries between countries and regions. However, it strengthens the public discussion around the issues of national languages, cultures, and mental characteristics. In this regard, the study of the Pakistani experience in the development of interethnic relations seems relevant from the point of view of analyzing the experience of implementing national policy in a multiethnic society, where interethnic contacts are multi-channel and intensive. The theoretical and methodological basis of the study was the results of field studies by foreign authors, as well as the work of domestic and Pakistani researchers. Keywords: Pakistani Punjabis, national identity, minority legal status, minority language.